2011
DOI: 10.1242/jcs.073916
|View full text |Cite
|
Sign up to set email alerts
|

Cortical localization of APC2 plays a role in actin organization but not in Wnt signaling inDrosophila

Abstract: SummaryThe tumor suppressor Adenomatous polyposis coli (APC) has roles in both Wnt signaling and in actin and microtubule organization. Within the cell, APC proteins have been reported to localize in the cytoplasm, at the cell cortex and in the nucleus. How these localizations relate to the functions of the protein is an aspect of APC biology that is poorly understood. Using Drosophila S2 cells, we have dissected the structural and functional requirements for the cortical localization of Drosophila APC2. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 58 publications
10
48
0
Order By: Relevance
“…To begin the characterization of these mutant proteins, we expressed them in Drosophila S2 cells. We have previously shown that APC2-FL localizes to the cortex in S2 cells, similar to its endogenous localization in embryonic cells (Zhou et al 2011). This localization requires both the Arm repeats and the C-terminal C30 domain (Zhou et al 2011), all of which are intact in our mutants.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…To begin the characterization of these mutant proteins, we expressed them in Drosophila S2 cells. We have previously shown that APC2-FL localizes to the cortex in S2 cells, similar to its endogenous localization in embryonic cells (Zhou et al 2011). This localization requires both the Arm repeats and the C-terminal C30 domain (Zhou et al 2011), all of which are intact in our mutants.…”
Section: Resultssupporting
confidence: 76%
“…We have previously shown that APC2-FL localizes to the cortex in S2 cells, similar to its endogenous localization in embryonic cells (Zhou et al 2011). This localization requires both the Arm repeats and the C-terminal C30 domain (Zhou et al 2011), all of which are intact in our mutants. As a test of the stability and functionality of our mutants, we asked whether they localized to the S2 cell cortex.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…A pool of APC localizes to the basolateral cortex or cell-cell junctions of vertebrate epithelial cells and tissues, and Drosophila APC2 likewise localizes to the cell cortex through interactions with the microtubule and actin cytoskeletons (NĂ€thke et al 1996;McCartney et al 1999McCartney et al , 2006Yu et al 1999;Rosin-Arbesfeld et al 2001;Langford et al 2006a,b;Grohmann et al 2007;Zhou et al 2011). In studies of nuclear export by APC, it was found that truncated APCs lacking cytoskeletal interaction regions shuttle between the nucleus and cytoplasm more efficiently than the full-length protein, suggesting that cytoskeletal interactions help to retain APC in the cytosol (Brocardo et al 2005), consistent with a role in cytoplasmic retention of b-catenin.…”
Section: Destruction Complex Localizationmentioning
confidence: 99%
“…APC proteins are thought to dimerize/ oligomerize as vertebrate APC proteins contain an N-terminal coiled-coil (Joslyn et al 1993) and Drosophila APC2 has been shown to self-associate in immunoprecipitation studies (Zhou et al 2011;Roberts et al 2012a). In addition, a yeast twohybrid study suggests that Drosophila APC1 and APC2 proteins can heterodimerize (Mattie et al 2010).…”
Section: An Apc2 Mutant Lacking All Bcat-binding Sites Is Also Functimentioning
confidence: 99%